Views and attitudes of teachers on the educational integration of students with autism spectrum disorders. (August 2015) - Cassimos, Dimitrios C.; Polychronopoulou, Stavroula A.; Tripsianis, Grigorios I.; Syriopoulou-Delli, Christine K.
Abstract Objectives: To investigate the views and attitudes of Greek teachers on educational and vocational integration of students with autism spectrum disorders (ASD). Methods: A statistically reliable sample of questionnaires distributed towards a diversified teacher population is evaluated. The mean values of teachers' responses are analyzed with respect to critical independent variables: previous relevant training; and/or experience. Results: The majority of the sample had a positive view towards the educational and vocational integration of students with ASD. Nevertheless, teachers appear to be sceptical in assuming that these students can be efficiently treated in their classroom. The vast majority of teachers maintain that students with ASD can be trained in technical vocation. However, the absence of support services is highly ranked as the most serious constraint for vocational integration. Conclusion: Training and experience substantially influenced teachers' views and attitudes in a positive way towards the integration of students with ASD.